A produção do cuidado no período gravídico-puerperal: experiência de mulheres usuárias de serviços públicos de saúde - Araújo, Lavinia Uchoa Azevedo de (2015)
Despite numerous government projects aimed at reorganizing and qualifying obstetric and neonatal care in Brazil, it remains problematic, with repercussions for maternal and newborn mortality and humanized care of both the mother and child. The objective of this study was to analyze the care provided to women during the pregnancy-puerperium cycle, based on reports of public health service users regarding their pregnancy and delivery experiences, using comprehensiveness and humanization as reference. The study applied a qualitative approach and the methodological strategy consisted of listening to the women, in order to identify, based on the meanings of their discourse concerning their experiences with health services, continuities and discontinuities of care during the pregnancy-puerperium cycle. Study participants were women who gave birth at a municipal public maternity, residents of Natal, Brazil, who at the time of the interviews, were between 10 and 42 days postpartum. Seven women reported their pregnancy and delivery experiences at public services. As interviews and observation took place, the material produced was also analyzed, in order to achieve simultaneous production and data analysis. Using systematization, a dialogue was established between the women’s discourses and production in the field of Collective Health, with respect to concepts and discussion about obstetric and neonatal care as well as the Comprehensiveness and Humanization of such care. Participant discourses underscored aspects related to prenatal care starting at pregnancy and its repercussions as well as prenatal monitoring by health services; aspects associated with care during labor and delivery, as well as those involved in postpartum in the maternity, both with respect to newborn and maternal careç and lastly, puerperium care after discharge from the maternity. Analysis of results sought to identify lines of continuity and discontinuity in the comprehensiveness and humanization of care. Based on these lines and as final contributions of the study, the following paths were proposed to achieve comprehensive and humanized production of health care for women during the pregnancy-puerperium cycle: Path 1- Reassess care in the maternal and newborn health network, aimed at comprehensiveness in terms of guaranteeing access to the various services and technological resources available to enhance health and life. Path 2- Reorganize work processes in order to attain comprehensive and humanized care for women in the pregnancy-puerperium cycle. Path 3 – Qualify the professional-user relationship in care management during the pregnancy-puerperium cycle. Path 4 – Invest in the qualification of communication processes in the different dimensions of care during the pregnancy-puerperium cycle.